1. The problem statement, all variables and given/known data ∫x2(√2+x) 2. Relevant equations ∫f(x) from a to b = f'(b) - f'(a) and substitution rule 3. The attempt at a solution I decided to make u=√(2+x), du= 1/2√(2+x) and when solving dx, i got dx= 2√(2+x) du. Substituting and then simplifying, I managed to get ∫2(x^2)u^2 du. But i can't go further from there. i can't find a way to get rid of the x2, I didn't get far using u= x2 or u=x+2 so I'm pretty sure i'm using the right substitution. I need help.